Drug-mediated disruption of the aging gut microbiota and mucosal immune system - Totleben, Lia; Thomas, Joel; Austin, Daniel (Frontiers in Aging, 2025)
The human gut microbiota is comprised predominantly of bacteria, and also includes archaea, fungi, and viruses. The gastrointestinal epithelium, mucosal barrier, and mucosal immune system balance protection against infection at mucosal entry points with symbiosis and tolerance to non-harmful organisms and antigens. Aging is associated with notable changes in both gut microbiota and mucosal immunity, including reduced microbial diversity, increased proportion of pathobionts relative to commensals, immunosenescence, and chronic inflammation. These changes may disrupt gastrointestinal function and homeostasis and increase susceptibility to infection and inflammatory conditions. Multiple drug classes are also associated with disruption of the gut microbiota and mucosal immunity, including antibacterials, proton pump inhibitors (PPIs), metformin, and steroidal and non-steroidal anti-inflammatory agents. This review describes the mechanisms by which these drugs affect the gut microbiota and mucosal immunity to provide perspective of the concurrent effects of drugs and age-related changes.